Driving Role of Interleukin‐2–Related Regulatory CD4+ T Cell Deficiency in the Development of Lung Fibrosis and Vascular Remodeling in a Mouse Model of Systemic Sclerosis. Issue 8 (28th June 2022) - Frantz, Camelia; Cauvet, Anne; Durand, Aurélie; Gonzalez, Virginie; Pierre, Rémi; Do Cruzeiro, Marcio; Bailly, Karine; Andrieu, Muriel; Orvain, Cindy; Avouac, Jérôme; Ottaviani, Mina; Thuillet, Raphaël; et al.
Abstract : Objective: Systemic sclerosis (SSc) is a debilitating autoimmune disease characterized by severe lung outcomes resulting in reduced life expectancy. Fra‐2–transgenic mice offer the opportunity to decipher the relationships between the immune system and lung fibrosis. This study was undertaken to investigate whether the Fra‐2–transgenic mouse lung phenotype may result from an imbalance between the effector and regulatory arms in the CD4+ T cell compartment. Methods: We first used multicolor flow cytometry to extensively characterize homeostasis and the phenotype of peripheral CD4+ T cells from Fra‐2–transgenic mice and control mice. We then tested different treatments for their effectiveness in restoring CD4+ Treg cell homeostasis, including adoptive transfer of Treg cells and treatment with low‐dose interleukin‐2 (IL‐2). Results: Fra‐2–transgenic mice demonstrated a marked decrease in the proportion and absolute number of peripheral Treg cells that preceded accumulation of activated, T helper cell type 2–polarized, CD4+ T cells. This defect in Treg cell homeostasis was derived from a combination of mechanisms including impaired generation of these cells in both the thymus and the periphery. The impaired ability of peripheral conventional CD4+ T cells to produce IL‐2 may greatly contribute to Treg cell deficiency in Fra‐2–transgenic mice. Notably, adoptive transfer of Treg cells, low‐dose IL‐2 therapy, or combination therapy changed the phenotype of Fra‐2–transgenic mice, resulting in a significant reduction in pulmonary parenchymal fibrosis and vascular remodeling in the lungs. Conclusion: Immunotherapies for restoring Treg cell homeostasis could be relevant in SSc. An intervention based on low‐dose IL‐2 injections, as is already proposed in other autoimmune diseases, could be the most suitable treatment modality for restoring Treg cell homeostasis for future research.